Investigation of nutritional status, life-style and eating habits in vocational Chinese college teachers: A cross-sectional survey - Ji , Chenming; Haq, Ijaz ul; Jing, Miao; Cui, Chunlan; Cheng , Liu; Tian, Qing; Meng, Xiumei; Wu, Qinmin; Jing, Li; Xu, Jelian; Khan, Abbas (Progress in Nutrition, 2021)
Background & objectives.Unhealthy dietary habits might harm teacher’s health. The present study was aimed at college teachers to investigate nutritional status, life-style and eating habits and find the association of nutritional status with the determinants. Methods: A cross-sectional survey was conducted in college teachers, including 33.3% males and 66.7% females. A validated self-administered questionnaire collects information regarding life-style factors and eating habits. Body composition was investigated through bioelectric impedance analysis (BIA). Multinomial and linear regressions were used for the association between dietary habits and nutritional status. Results.Obesity/overweight/high body fats, poor sleep quality and neck and back problems were more common among the respondents. Work/life stress and life-style problems were affecting health status. Animal-source food had a greater risk of increasing BMI (AOR = 2.9, P